Pembelajaran Teorema-Teorema Klasik Dalam Struktur Aljabar Menggunakan GAP - Sisilia Sylviani (Universitas Muhammadiyah Ponorogo, 2016)
This paper gives an idea of the methods of learning algebra structure using the software GAP (Group, Algorithm, and Programming). Classic theorem is often used in the subject of algebraic structures, including finite abelian group theorem, Lagrange theorem, and isomorphism theorem. Understanding the theorem and the proof is not easy for students. This paper offered a method that can be used by students when studying a theorem through some structured experiments using GAP. Such experiments would eventually lead them to make a conjecture. So hopefully the students can construct an understanding of a theorem, and it will become much easier for them to remember and understand the theorem.Keywords: classic theorem, abstract algebra, GAP, Algebraic